DAMPAK PEMBANGUNAN PERKEBUNAN KARET-RAKYAT TERHADAP KEHIDUPAN PETANI DI RIAU - SADIKIN, IKIN; IRAWAN, RUDI (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 6, No. 3 November 2006, 2012)
Meaning sense of this paper is to explain and to analyze development process (in smallholder rubber sub sector) that have done by the government in Riau Province. Agricultural system which plantation system is a compatible model with in local people. Afterwards for to explain reality and to phenomenon analysis and what dynamic happen in that development, so analysis and it’s examine pressured to literacy study and others theory and to use information’s. The development problems appear because of the modernization strategy that applied by the government less accommodating local potential’s, with the result that local societies think that the development are not for them. And finally, development programs less popular in the societies and can not supported by the people, so consequences social change not yet.
Keywords: Development, Smallholder Rubber, Farmer Income